Lunatibacter salilacus gen. nov., sp. nov., a member of the family Cyclobacteriaceae, isolated from a saline and alkaline lake sediment. Issue 2 (6th February 2021) - Han, Ming-Xian; Huang, Jian-Rong; Jiang, Hong-Chen; Fang, Bao-Zhu; Xie, Yuan-Guo; Li, Wen-Jun
Abstract : A non-motile, Gram-staining negative, catalase- and oxidase-positive, crescent-rod shaped bacterium, designated strain CUG 91308 T, was isolated from a sediment sample of Qinghai Lake, Qinghai Province, China. Colonies on OSM agar were round, smooth, flat and pinkish-orange in colour. Strain CUG 91308 T could grow at 15–37 °C, pH 6–12 and in the presence of up to 7.0 % NaCl (w/v). Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain CUG 91308 T belonged to the family Cyclobacteriaceae and formed a clade with the genus Lunatimonas in the phylogenetic tree, but separated from any species of the known genera within the family. The genomic DNA G+C content is about 42.1 %. The predominant fatty acids (>10 %) were iso-C15 : 0 (21.1 %), summed feature 3 (C16 : 1   ω 7c / C16 : 1   ω 6c / iso-C15 : 0 2OH) (14.3 %), iso-C17 : 0 3OH (12.3 %) and summed feature 9 (iso-C17 : 1   ω 9c / C16 : 0 10-methyl) (10.6 %). The polar lipids of strain CUG 91308 T were phosphatidylethanolamine (PE) and four unidentified polar lipids. Strain CUG 91308 T contained MK-7 as the major respiratory quinone. On the basis of phenotypic, genotypic and phylogenetic data, strain CUG 91308 T represents a novel species of a novel genus in the family Cyclobacteriaceae, for which the name Lunatibacter salilacus gen. nov., sp. nov. is proposed. The type strain of the proposed new isolate is CUG 91308 T (=KCTC 62636 T =CGMCC 1.13593 T ).